Butyrylcholinesterase levels correlate with surgical site infection risk and severity after colorectal surgery: a prospective single-center study - Verras, Georgios-Ioannis; Mulita, Francesk (Frontiers in surgery, 2024)
Surgical site infections (SSIs) after colorectal surgery remain a significant concern, which warrants effective predictive markers for prompt diagnosis and treatment. Butyrylcholinesterase (BChE), a non-specific cholinesterase enzyme, has been correlated with the risk of hepatic dysfunction progression and, more recently, infectious diseases and septic shock with ongoing research into the utility of BChE in multiple systemic inflammatory conditions. Whether these preliminary results can be translated into predicting infection after colorectal surgery remains in remains in question. This prospective study aimed to assess BChE's potential as a predictive marker for surgical site infections and anastomotic leaks after colorectal surgery. This single-center prospective study (11/2019-05/2023) enrolled 402 patients who underwent colorectal surgery. BChE levels were measured at four postoperative time points. The primary endpoints focused on BChE's association with complications, particularly surgical site infections (SSIs). Further known predictors of SSI were utilized to construct multivariable models to assess for independent association with SSI development. During the third and fifth day postsurgery, SSI patients had significantly lower mean BChE levels (3.90 KU/L vs. 4.54 KU/L -value < 0.05, and 4.14 KU/L vs. 4.73 KU/L, -value < 0.05; -test, respectively). However, multivariate analysis revealed that when adjusted for other factors, low BChE levels on the first postoperative day were associated with 2.6 times higher odds of developing SSI (OR: 2.6, 95%CI: 1.3-3.9, value < 0.05). Similar results were found for low BChE levels on the third postoperative day as they were associated with a. 2.53 times higher odds for developing SSI (OR: 2.5, 95%CI: 1.27-3.87, -value < 0.05) when adjusted for other factors. In conclusion, in this prospective observational study, low levels in the first and third postsurgery were associated with an increased risk for the development of SSIs but not sepsis.